Hepatotoxicity of the pesticides imazalil, thiacloprid and clothianidin – Individual and mixture effects in a 28-day study in female Wistar rats. (June 2020) - Alarcan, Jimmy; Waizenegger, Julia; Solano, Marize de Lourdes Marzo; Lichtenstein, Dajana; Luckert, Claudia; Peijnenburg, Ad; Stoopen, Geert; Sharma, Raju Prasad; Kumar, Vikas; Marx-Stoelting, Philip; Lampen, Alfonso; Braeuning, Albert
Abstract: Humans are exposed to pesticide residues through various food products. As these residues can occur in mixtures, there is a need to investigate possible mixture effects on human health. Recent exposure studies revealed the preponderance of imazalil, thiacloprid, and clothianidin in food diets. In this study, we assessed their toxicity alone and in binary mixtures in a 28-day gavage study in female Wistar rats. Five dose levels (up to 350 mg/kg bw/day) ranging from a typical toxicological reference value to a clear effect dose were applied. Data show that the liver was a target organ of all pesticides and their mixtures. Increases in liver weight were observed and histopathological examination revealed centrilobular hepatocellular hypertrophy and cytoplasm degeneration for all treatment conditions. No accumulation of hepatic triglycerides was reported. Tissue residue analysis showed altered pesticide residues in the liver and the kidney when being in mixture as compared to the levels of pesticide residues for the single compound treatment, indicating possible toxicokinetic interactions. Overall, all mixtures appeared to follow the additivity concept, even though quantitative analysis was limited for some endpoints due to the semi-quantitative nature of the data, raising no specific concern for the risk assessment of the examined pesticides. Highlights: A 28-day study in rats was conducted to assess mixture effects of pesticides. Increases in absolute and relative liver weight were observed. Histopathology revealed hepatocellular hypertrophy and cytoplasm degeneration. Alterations in the residue levels were noticed for mixtures in the liver and kidney. Mixtures of pesticides presumably follow additivity concept.